Talking back to radio - Huggins-Rao, Sheila; Leclair, Mark (Technical Centre for Agricultural and Rural Cooperation, 2009)
Radio is often considered to be a one-way medium, but the African Farm Radio Research Initiative is investigating ways of combining radio and ICTs to gather content and to share information among farming communities throughout rural Africa.